Measurement of Interleukin-33 (IL-33) and IL-33 Receptors (sST2 and ST2L) in Patients with Rheumatoid Arthritis - Hong, Yeon-Sik; Moon, Su-Jin; Joo, Young-Bin; Jeon, Chan-Hong; Cho, Mi-La; Ju, Ji Hyeon; Oh, Hye-Jwa; Heo, Yu-Jung; Park, Sung-Hwan; Kim, Ho-Youn; Min, Jun-Ki (Journal of Korean medical science, 2011)
The interleukin-33 (IL-33)/ST2 pathway has emerged as an intercellular signaling system that participates in antigen-allergen response, autoimmunity and fibrosis. It has been suggested that IL-33/ST2 signaling has been involved in the pathogenesis of rheumatoid arthritis (RA), because IL-33 and its receptor have been specifically mapped to RA synovium. The aim of this study was to determine the levels of IL-33 and sST2 in sera and synovial fluids in patients with RA. The serum level of IL-33 was significantly higher in patients with RA (294.9 ± 464.0 pg/mL) than in healthy controls (96.0 ± 236.9 pg/mL, P = 0.002). The synovial fluid level of IL-33 was significantly higher in RA patients than in osteoarthritis patients. The level of serum sST2 was higher in RA patients than in healthy controls (P = 0.042). A significant relationship was found between the levels of IL-33 and IL-1β (r = 0.311, P = 0.005), and IL-33 and IL-6 (r = 0.264, P = 0.017) in 81 RA patients. The levels of IL-33, sST2 and C-reactive protein decreased after conventional disease-modifying antirheumatic drugs treatment in 10 patients with treatment-naïve RA. Conclusively, IL-33 is involved in the pathogenesis of RA and may reflect the degree of inflammation in patients with RA.